New replacement name for the genus Latitergum Yu, Ślipiński, Leschen, Ren & Pang, 2014 (Insecta: Coleoptera: Trogossitidae) - Zhang, Yubo (Zootaxa, 2021)
Yu, Ślipiński, Leschen, Ren and Pang (2014) established the trogossitid fossil genus Latitergum with the type species Latitergum glabrum Yu, Ślipiński, Leschen, Ren & Pang, 2014 from China (Jiulongshan Formation, Inner Mongolia). So far, this genus includes only type species and it is recorded only from China. It was used as a valid generic name in the family Trogossitidae (Insecta: Coleoptera).